Voyages oniriques dans l’album iconotextuel - CONNAN-PINTADO, Christiane (Ondina - Ondine, 2019)
In this article we will study the dream stories in picture books, when they take form of a journey. These dreamlike journeys generally remain in the nursery, but they transfigure the familiar world. Some picture books, meant for a larger public, tell the story of a quest and a journey back in time, in search of childhood or of another life. Through the dialogue of text and images, the iconotextual picture book feeds on artistic and literary references that cultivate the fantastic and wonderful genres. They thus provide the characters and the readers with a sense of “disturbing strangeness”. Keywords: Dream trip; Picture book; children’s room; childhood; memory; fantastic